Lidt om politisk ekstremisme: – i Henrik Pontoppidans forfatterskab - de Thurah, Christian (Pontoppidaniana, 2025)
Abstract Extremist characters and extreme opinions about various subjects, such as love, religion and society, appear frequently in Henrik Pontoppidan´s work. In this essay, Christian de Thurah takes a closer look at a number of his minor texts that deal with political extremism. The conclusion is that the political discussions in these texts are not so much about politics in a narrow sense as they are a broader criticism of a civilisation that has become alienated from what the author sees as the fundamental laws of life, of nature. But the extreme criticism of civilisation does not stand alone and unchallenged, as it is counterbalanced by more low-voiced but nevertheless important “soft” values, first of all love. This ambiguity (“tvesyn”) is typical of Henrik Pontoppidan as an author.